Large radicular cyst compressing the mandibular canal: a case report - Andika, Steve Yosua; Yunizar, Vania Rizky; Audry Arifin, Sariyani Pancasari; Anggraeni, Rezky (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: To describe radicular cysts and differentiate them from radiographically similar cysts such as odontogenic keratocysts. Case Report: A 21-year-old female patient presented to the Dental and Oral Hospital with a primary complaint of residual root fragments in the left mandibular region, for which she requested extraction. Extraoral clinical examination revealed no facial asymmetry, swelling, or tenderness, and the region was asymptomatic upon palpation. The patient reported no relevant systemic medical history. Panoramic radiographic examination demonstrated a well-defined unilocular radiolucent lesion extending from the apical third of tooth 36 to the periapical areas of teeth 35, 37, and 38. Given the limitations in diagnostic detail offered by conventional periapical radiography, a Cone-Beam Computed Tomography (CBCT) scan was subsequently performed. Multiplanar reconstruction images from the CBCT revealed a radiolucent lesion extending from the periapical area of tooth 35, with evidence of compression on the mandibular canal. Conclusion: Radicular cysts are the most common type of odontogenic cyst and are associated with dental inflammation. Radicular cysts and OKCs have a similar radiographic appearance, leading to confusion between the two. Cone Beam Computed Tomography (CBCT) offers three-dimensional imaging that allows a comprehensive assessment of the lesion's size, extent, and relationship to adjacent anatomic structures, allowing the characteristics of both radicular lesions and OKCs to be clearly demonstrated. The characteristics of each lesion can be clearly described, making CBCT a very helpful modality in these cases. Keywords: Cone Beam Computed Tomography, odontogenic cyst, radicular cyst